Changes in body mass during weight loss treatment – a two-year prospective study - Krekora-Wollny, Katarzyna; Suliga, Edyta (Medical Studies/Studia Medyczne, 2017)
Introduction : A reduction of 5% to 10% of body mass is related to a significantly lower risk of the occurrence of conditions whose underlying cause is obesity. Aim of the research : The analysis of body mass and body composition changes in overweight and obese patients undergoing weight loss treatment. Material and methods : A total of 129 overweight and obese individuals qualified for the study. All patients were instructed to follow a healthy, balanced diet based on the nutritional standards. The patients were subjected to anthropometric measurements and body composition tests by means of bioimpedance analysis. The analysis included measurements performed 3, 6, 12, and 24 months after the first appointment. One-factor analysis of variance was applied to test the changes of body mass and composition in the following months. Results : The average body mass index of the patients decreased on consequent follow-up appointments from 33.8 ±5.17 kg/m 2 to 31.8 kg/m 2 after 3 months, 30.5 kg/m 2 after 6, and 29.6 kg/m 2 after 12 months, and remained at this level for another 12 months. The average amount of adipose tissue decreased from 40.98 ±7.1% to 38.34% after 3 months, 36.26% after 6, 34.69% after 12, and 34.43% after 24 months. Conclusions : Due to lifestyle adjustments, about 70% of the subjects achieved satisfactory results in the weight-loss process. The majority of these individuals were able to maintain satisfactory body mass loss in the longer term. After 24 months of observation, in about 1/3 of the individuals, a tendency to an increase in body weight and adipose tissue was observed, and in some cases a total regain of pre-treatment body mass. In order to improve the effectiveness and stability of the weight-loss process, it is necessary to conduct further studies aimed at identifying the causes for this phenomenon.